2017
DOI: 10.3201/eid2311.170480
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women Hospitalized with Chikungunya Virus Infection, Colombia, 2015

Abstract: Personnel in charge of obstetric populations should watch for cases of chikungunya virus‒induced sepsis with hypoperfusion and organ dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 34 publications
1
46
0
3
Order By: Relevance
“…Of the 563 identified articles, 13 [ 27 , 45 56 ] (from 8 cohorts) with pertinent data were included in the quantitative data synthesis ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 563 identified articles, 13 [ 27 , 45 56 ] (from 8 cohorts) with pertinent data were included in the quantitative data synthesis ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…By extrapolation also of these data [ 27 , 51 , 55 ], the overall pooled-MTCT-risk across cohorts was at least 15.5% (95% CIs: 13.57%-17.53%; 206/1331) ( Table 1 ; S3 and S4 Tables) and the risk among maternal infections during the intrapartum period was at least 50.0% (95% CIs: 34.90%-65.10%; 23/46) vs 0% (0/712) among antepartum/peripartum maternal infections. The timing of maternal infections was analyzed only in three cohorts [ 27 , 53 , 56 ]; 5% of all analyzed maternal infections in these three cohorts occurred during the intrapartum period. Results by REM synthesis of data were similar (MTCT-overall risk: at least 12.6% [95% CIs 4.47%-20.77%]; MTCT-risk-intrapartum infections: at least 50.3% [3.75%-96.93%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Escobar et al, reported clinical manifestations of neonatal chikungunya including fever, irritability, rash and hyperalgesia syndrome. 7 Diffuse limb edema, meningoencephalitis and bullous dermatitis were other rare manifestations. Encephalopathy in neonates has been associated with chikungunya virus as well as zika virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…In Argentina, the transmitting mosquito Aedes albopictus was restricted to the northeastern province of Misiones, while the A. aegypti was present from the northern border to the Patagonian city of Neuquén 5 . In this same period, in Colombia, CHIKV infection was an important complication observed in pregnant women, leading to admission to intensive care due to sepsis 8 .…”
mentioning
confidence: 99%